A Reversible Cytotoxic Lesion of the Corpus Callosum Developing after a Rapid Alteration in Cerebrospinal Fluid Pressure/Volume in a Patient with New Daily Persistent Headache - Todd D. Rozen; Hector A. Robles (Case Reports in Neurological Medicine)
A case is presented of a woman with a history of daily persistent head pressure and dizziness who developed a cytotoxic lesion of the splenium of the corpus callosum after an acute withdrawal of chronic acetazolamide treatment and then, in quick succession, a CSF pressure/volume drop with a lumbar puncture. This is the first documentation that rapid alterations of CSF pressure/volume may trigger cytotoxic lesions in the central nervous system.